Body image concern and eating disorder symptoms among elite Icelandic athletes - Kristjánsdóttir, H.; Sigurðardóttir, P.; Jónsdóttir, S.; Porsteinsdottir, G.; Saavedra, J. (International Journal of Environmental Research and Public Health, 2019)
The aim of this study was to analyse body image concerns and symptoms of eating disorders in elite Icelandic athletes according to their sex, and sport practiced. The participants were 755 athletes (24.8 ± 3.5 years in age) who compete at the highest possible level in Iceland. Representing 20 different sports, they were divided into five sports groups. Three questionnaires were used: the Body Shape Questionnaire to assess body image concerns; the Bulimia Test-Revised to assess the main symptoms of bulimia; and the Eating Disorder Examination Questionnaire to identify disordered eating attitudes and behaviours. A chi-squared test was used to analyse differences in prevalence of body image concern and eating disorders, a t-test for the differences between men and women, and a one-way ANOVA to compare the different sports. The main findings were that 17.9% of the athletes presented severe or moderate body image dissatisfaction, and 18.2% (25.3% of the women) were above the clinical cutoff for body image concern. Women`s scores were higher than men`s (whole sample and ball games) in all variables except restraint. These results seem to point to the existence of a real problem that athlete, coaches, doctors, and institutions need to take into account.